Topological structure and experimental investigation of a novel whole tire bead. (May 2021) - Li, Yong; Sun, Xunhua; Song, Julan; Zhang, Shoudong; Han, Shanling
Abstract: The tire bead area is a vulnerable part of the tire. By analyzing its development trend, a novel topological structure of the whole tire bead was put forward. Firstly, the feasibility of the whole tire bead is preliminarily proved easy to achieve topology improvement, which can exceed the limit of the shape of the normal steel/rubber composite bead. Secondly, through finite element analysis it showed that the whole tire bead tire is superior to the normal tire bead tire in terms of tire-rim tightening force, carcass cord stress, cord endpoint stress, and grounding footprint, etc. This structure reduces the Von Mises stress in the bead area by 40%. Finally, the research designed a complete set of production technologies from whole tire bead processing to tire validation which was well realized. The indoor comparative durability test of the two structures showed that the temperature of the whole tire bead was reduced by 5 °C and the durability time was increased by more than 50%, which indicated that the durability and temperature rise performance of the whole tire bead are better than that of normal tires. This structure has broad prospects in the application of heavy-duty tires. Graphical abstract: The bottom of the whole bead has an oblique angle of 3°, which can form a closer fit with the rim. The stress of the whole bead is much lower than that of the normal steel wire bead at the outer end point of the bead wrapper and the end point of the carcass cord, which is beneficial to reduce the rubber delamination caused by the outer end point of the wrapper and the end point of the cord. The comparative test of the whole bead and the normal bead showed that the bead temperature of the whole bead was reduced by about 5 °C before damage. Unlabelled Image Highlights: A new topological bead of tire was designed by breaking the normal shape limits. This structure reduces the Mises stress at the bead area by 40% through FEA. Its special processing technology was well realized in production. Its durability time was increased by more than 50% in the indoor test.